Particle-vortex and Maxwell duality in the AdS(4) x CP3/ABJM correspondence - Murugan, Jeff; Nastase, Horatiu [UNESP]; Rughoonauth, Nitin; Shock, Jonathan P. (Springer, 2014)
We revisit the notion of particle-vortex duality in abelian theories of complex scalar fields coupled to gauge fields, formulating the duality as a transformation at the level of the path integral. This transformation is then made symmetric and cast as a self-duality that maps the original theory into itself with the role of particles and vortices interchanged. After defining the transformation for a pure Chern-Simons gauge theory, we show how to embed it into (a sector of) the (2 + 1)-dimensional ABJM model, and argue that this duality can be understood as being related to 4-dimensional Maxwell duality in the AdS(4) x CP3 bulk.
Keywords: Duality in Gauge Field Theories; Solitons Monopoles and Instantons; AdS-CFT Correspondence